Analisis Perbandingan Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing dan Variable Costing dalam Menentukan Harga Jual Pada UMKM - Santi Median; Sihabudin; Robby Fauji (Journal of Trends Economics and Accounting Research, 2023)
This study aims to find out how the comparative analysis of the calculation of the cost of production in determining the selling price at Karisma Rahayu Sejati uses the variable costing and full costing methods. In this study, using a quantitative descriptive method. Sources of data used are primary data and secondary data. Interview, observation, and documentation techniques were used as data collection techniques. This study examines the calculation of the cost of production to determine the selling price of Karisma Rahayu Sejati. The problem is, Karisma Rahayu Sejati experienced a decline in sales after the selling price of their products was increased. So that in the calculation of the cost of production, there are still costs that are not included. The results of this study indicate that by using the full costing method the calculation of the cost of production is higher than the calculations made by Karisma Rahayu Sejati and using the variable costing method the calculation of the cost of production is lower. because by using the full costing method all cost elements, both variable costs and fixed costs are included and classified according to cost classification. So the most appropriate and efficient method is the full costing method.